New Joint Design to Create a More Natural and Efficient Biped - Giuseppina Gini; Umberto Scarfogliero; Michele Folgheraiter (Applied Bionics and Biomechanics)
This paper presents a human-oriented approach to design the mechanical architecture and the joint controller for a biped robot. Starting from the analysis of the human lower limbs, we figured out which features of the human legs are fundamental for a correct walking motion, and can be adopted in the mechanical design of a humanoid robot. We focus here on the knee, designed as a compliant human-like knee instead of a classical pin-joint, and on the foot, characterised by the mobility and lightness of the human foot. We implemented an elastic actuator, with a simple position control paradigm that sets the joint stiffness in real time, and developed the basic controller. Results in simulation are discussed. In our approach the robot gains in adaptability and energetic efficiency, which are the most challenging issues for a biped robot.